Synthesis of tetrahalide dianions directed by crystal engineering1. Issue 35 (21st September 2015) - Pan, F.; Puttreddy, R.; Rissanen, K.; Englert, U.
<x xml:space="preserve">Abstract</x> The analogy between hydrogen bonds and halogen bonds was used to synthesize the unstable [X⋯I–I⋯X]2− species by trapping I2 in the channels of macrocyclic compounds.